Detection of topological matter with quantum gases. Issue 10 (31st July 2013) - Spielman, I. B.; Blatt, Rainer; Bloch, Immanuel; Cirac, Ignacio; Zoller, Peter
<x xml:space="preserve">Abstract</x> Creating and measuring topological matter – with non‐local order deeply embedded in the global structure of its quantum mechanical eigenstates – presents unique experimental challenges. Since this order has no signature in local correlation functions, it might seem experimentally inaccessible in any macroscopic system; however, as the precisely quantized Hall plateaux in integer and fractional quantum Hall systems show, topology can have macroscopic signatures at the system's edges. Ultracold atoms provide new experimental platforms where both the intrinsic topology and the edge behavior can be directly measured. This article reviews, using specific examples, how non‐interacting topological matter may be created and measured in quantum gases. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>